Consequences Of Long-Term Bacteria’s Exposure To Silver Nanoformulations With Different PhysicoChemical Properties - Kędziora A (Dove Medical Press, 2020)
Anna Kędziora, 1 Maciej Wernecki, 1 Kamila Korzekwa, 1 Mateusz Speruda, 1 Yuriy Gerasymchuk, 2 Anna Łukowiak, 2 Gabriela Bugla-Płoskońska 1 1Department of Microbiology, Institute of Genetics and Microbiology, University of Wroclaw, Wroclaw, Poland; 2Trzebiatowski Institute of Low Temperature and Structure Research PAS in Wrocław, Wroclaw, PolandCorrespondence: Gabriela Bugla-Płoskońska; Anna KędzioraDepartment of Microbiology, Institute of Genetics and Microbiology, University of Wroclaw, Ul. Przybyszewskiego 63-77, Wroclaw, PolandTel +48 71 375 63 23Email gabriela.bugla-ploskonska@uwr.edu.pl; anna.kedziora@uwr.edu.plPurpose: Resistance to antibiotics is a major problem of public health. One of the alternative therapies is silver – more and more popular because of nanotechnology development and new possibilities of usage. As a component of colloid, powder, cream, bandages, etc., nanosilver is often recommended to treat the multidrug-resistant pathogens and we can observe its overuse also outside of the clinic where different physicochemical forms of silver nanoformulations (e.g. size, shape, compounds, surface area) are introduced. In this research, we described the consequences of long-term bacteria exposure to silver nanoformulations with different physicochemical properties, including changes in genome and changes of bacterial sensitivity to silver nanoformulations and/or antibiotics. Moreover, the prevalence of exogenous resistance to silver among multidrug-resistant bacteria was determined.Materials and Methods: Gram-negative and Gram-positive bacteria strains are described as sensitive and multidrug-resistant strains. The sensitivity of the tested bacterial strains to antibiotics was carried out with disc diffusion methods. The sensitivity of bacteria to silver nanoformulations and development of bacterial resistance to silver nanoformulations has been verified via determination of the minimal inhibitory concentrations. The presence of sil genes was verified via PCR reaction and DNA electrophoresis. The genomic and phenotypic changes have been verified via genome sequencing and bioinformatics analysis.Results: Bacteria after long-term exposure to silver nanoformulations may change their sensitivity to silver forms and/or antibiotics, depending on the physicochemical properties of silver nanoformulations, resulting from phenotypic or genetic changes in the bacterial cell. Finally, adaptants and mutants may become more sensitive or resistant to some antibiotics than wild types.Conclusion: Application of silver nanoformulations in the case of multiple resistance or multidrug-resistant bacterial infection can enhance or decrease their resistance to antibiotics. The usage of nanosilver in a clinic and outside of the clinic should be determined and should be under strong control. Moreover, each silver nanomaterial should be considered as a separate agent with a potential different mode of antibacterial action.Keywords: silver, antibiotics, resistance, sil genes, mutant, adaptant